Quantifying the relative importance of transcellular and paracellular ion transports to coral polyp calcification - Hohn, Sönke; Merico, Agostino (Frontiers in Earth Science, 2015)
Ocean acidification due to rising atmospheric pCO2 slows down coral calcification and impedes reef formation, with deleterious consequences for the diversity of reef ecosystems. Such interactions contrast with the capacity of corals to actively regulate the chemical composition of the calcifying fluid where calcification occurs. This regulation involves the active transport of calcium, bicarbonate, and hydrogen ions through epithelium cells, the transcellular pathway. Ions can also passively diffuse through intercellular spaces via the paracellular pathway, which directly exposes the calcifying fluid to changes in ocean chemistry. Although evidence exists for both pathways, their relative contribution to coral calcification remains unknown. Here we use a mathematical model to test the plausibility of different calcification mechanisms also in relation to ocean acidification. We find that the paracellular pathway generates an efflux of calcium and carbonate from the calcifying fluid, causing a leakage of ions that counteracts the concentration gradients maintained by the transcellular pathway. Increasing ocean acidity exacerbates this carbonate leakage and reduces the ability of corals to accrete calcium carbonate.